2009
DOI: 10.1536/ihj.50.711
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Myocardial Infarction Time Course in Women Compared With Men in Upper Silesia Population in 30 Day Follow-Up

Abstract: SummaryThe aim of the study was to compare the course of myocardial infarction in women versus men in Upper Silesia, an industrial region in the south of Poland.The study comprised 1003 patients with either ST-elevation myocardial infarction (STEMI) or non-ST-elevation myocardial infarction (NSTEMI). The patients were divided into group 1 (300 females) and group 2 (control, 703 males). The groups differed significantly with respect to age, incidence of hypertension, diabetes, and smoking. In group 1 STEMI occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Elderly women who have survived a myocardial infarction frequently visit their doctors complaining of chest pain and have significantly higher mortality rate, target lesion reoclussion (3,24), postinfarction refractory anaemia in the short term, and AMI in the long term (25,26). Although cardiac troponin is a pivotal marker of cardiac ischaemic injury/necrosis (27), a single negative cTnI test is not sufficient to disregard the presence of AMI because of its low sensitivity in the first 3 h of chest pain onset (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…Elderly women who have survived a myocardial infarction frequently visit their doctors complaining of chest pain and have significantly higher mortality rate, target lesion reoclussion (3,24), postinfarction refractory anaemia in the short term, and AMI in the long term (25,26). Although cardiac troponin is a pivotal marker of cardiac ischaemic injury/necrosis (27), a single negative cTnI test is not sufficient to disregard the presence of AMI because of its low sensitivity in the first 3 h of chest pain onset (2,3).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of VA during hospitalization for ACS in our study is similar to that reported in previous studies of patients with STEMI and NSTEMI enrolled in randomized clinical trials (RCT). 7 Additionally, RCT patients were more likely to be men 11 13 and have a history of coronary heart disease 14 and hyperlipidemia, 15 and have Killip class >I on admission. Our baseline findings revealed less coronary artery disease and hyperlipidemia compared with these published studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that poor clinical outcomes in women are related to suboptimal [26][27][28][29]. Conversely, several lines of evidence indicate that guidelines-compliant treatment in women and men results in significant improvements in outcomes [30]. It is known that a delay in the application of invasive treatment significantly worsens the prognosis of patients with STEMI [31].…”
Section: Bmi -Body Mass Index (Kg/m 2 ) MI -Myocardial Infarction Pmentioning
confidence: 99%